Reassessing the value premium : Evidence from intangible-driven mispricing - Ahmad, Fawad (Journal of Economics and Business, 2026)
The predictability of key-value metrics, such as the book-to-market ratio, has declined over the past decade, primarily due to the decreasing reliability of book equity. This trend is particularly evident because traditional value-to-market measures often fail to account for intangible assets. This paper examines the impact of mispricing signals associated with a firm's intangible intensity on the value premium. The findings indicate that value stocks with high intangible intensity tend to outperform growth stocks with low intangible intensity. However, there is no significant difference in returns between value stocks with low intangible intensity and growth stocks with high intangible intensity. The results suggest that an investment strategy combining a long position in value stocks with high intangible intensity and a short position in growth stocks with low intangible intensity is associated with mispricing. Risk-based factors cannot account for the return differences attributable to the long-short strategy. Moreover, the results confirm that the decline in the performance of value anomalies is largely attributable to the absence of intangible information in traditional value-to-market measures, a key driver of the value effect. These findings further emphasize the importance of considering intangible factors as a key predictor when assessing a firm's competitive position and potential for value creation. Integrating intangible intensity into investment strategy development can enhance the effectiveness of value investing. Importantly, these findings are consistent with a mispricing interpretation related to the complexity of processing intangible information, although alternative explanations cannot be fully ruled out. Because firms’ intangible investment decisions are endogenous and may reflect unobserved characteristics, such as managerial quality or innovation prospects, our results should be interpreted as documenting robust cross-sectional associations rather than causal effects.
Keywords: Intangibles; Mispricing; Value premium